The State of Cotton Cultivation in the Khorezm People's Soviet Republic - Ismatovich, Samadov (Indonesian Journal Publisher, 2025)
After the establishment of the Khorezm People's Soviet Republic, the most pressing task for the government was the development of the national economy. To achieve this, the restoration of agriculture was of primary importance. Cotton cultivation, being the most profitable sector of agriculture, had faced severe difficulties at the time, and productivity had significantly decreased. This article outlines the measures taken to develop the cotton sector in the Khorezm People's Soviet Republic after its formation. The state of cotton cultivation in the Khorezm People's Soviet Republic (XXSR) was an essential aspect of the region's agricultural recovery following its establishment in 1920. After the revolution and the formation of the Soviet government in Khorezm, the primary objective was to restore the economy, with a particular focus on revitalizing agriculture, which had suffered greatly during the upheaval. Cotton, as one of the most lucrative crops in the region, became a central focus for the new Soviet authorities. The Khorezm People's Soviet Republic aimed to increase cotton production to meet the growing demand in Soviet Russia, which relied heavily on Khorezm's cotton as an important raw material. In the early years, the cotton industry was severely damaged by the political instability and war. However, the Soviet government took several steps to restore it. One of the first priorities was addressing land and water issues, which had been significant barriers to cotton production. Following the redistribution of land and the nationalization of large estates, the government aimed to modernize irrigation systems, build new canals, and introduce mechanized pumps for more efficient water usage. To encourage cotton cultivation, farmers were provided with low-interest loans, tax exemptions, and other incentives. The government also worked to ensure that cotton was the primary crop, often at the expense of food crops, which led to food shortages in some areas. By 1923, the cotton-growing area had expanded significantly, and production began to rise steadily. The cotton industry was largely controlled by state-run entities, such as the Russia-Khorezm Cotton Company, which handled the purchase, processing, and distribution of cotton. While the cotton industry was revitalized, the entire harvest was often sent to Russia, leaving little to support local economic development or food security.